Back Cover: Synthetic Origin of Tramadol in the Environment (Angew. Chem. Int. Ed. 1/2016). Issue 1 (9th December 2015) - Kusari, Souvik; Tatsimo, Simplice Joel N.; Zühlke, Sebastian; Spiteller, Michael
Abstract : Tramadol was recently found in roots of Sarcocephalus latifolius and other plants as well as in soil and water in Northern Cameroon, which has led to an extensive discussion on its natural or synthetic origin. In their Communication onpage 240 ff., M. Spiteller et al. unambiguously confirm that synthetic tramadol has indeed contaminated the environment in rural as well as densely populated areas of Northern Cameroon.